Construction of Well‐Defined Redox‐Responsive CO2‐Based Polycarbonates: Combination of Immortal Copolymerization and Prereaction Approach. Issue 9 (21st March 2017) - Liu, Shunjie; Zhao, Xun; Guo, Hongchen; Qin, Yusheng; Wang, Xianhong; Wang, Fosong
Abstract : By specific control, starter‐based redox‐responsive polycarbonates from CO2 and epoxides are reported by combination of immortal polymerization and prereaction approach. Via judicious use of 3, 3′‐dithiodipropionic acid as starter, the initiating group of traditional binary catalyst system is completely suppressed, resulting in pure starter‐initiated polymer. The polymer is liable under reducing conditions and can be further modified by cross metathesis. Abstract : Due to the axial group initiation in traditional (salen)CoX/quaternary ammonium catalyst system, it is difficult to construct single active center propagating polycarbonates for copolymerization of CO2 /epoxides. Here a redox‐responsive poly(vinyl cyclohexene carbonate) (PVCHC) with detachable disulfide‐bond backbone is synthesized in a controllable manner using (salen)CoTFA/[bis(triphenylphosphine)iminium, [PPN]TFA binary catalyst, where the axial group initiation is depressed by judiciously choosing 3, 3′‐dithiodipropionic acid as starter. While for those comonomers failing to obtain polycarbonate with unimodal gel permeation chromatography (GPC) curve, a versatile method is developed by combination of immortal copolymerization and prereaction approach, and functional aliphatic polycarbonates having well‐defined architecture and narrow polydispersity can be prepared. The resulting PVCHC can be further functionalized with alkenes by versatile cross‐metathesis reaction to tune the physicochemical properties. The combination of immortal polymerization and prereaction approach creates a powerful platform for controllable synthesis of functional CO2 ‐based polycarbonates.